Pendidikan Kewirausahaan dalam Islam - Maulana, Fikri (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2019)
This research is a literature study (library research) and with a thematic interpretation method. The interpretation method is used to dissect the verses relating to entrepreneurial motivation. After conducting a study of entrepreneurial motivation in Islam, namely in the Koran and Hadith, found several things as follows: (1) Alquran's view of entrepreneurial motivation can be found in Surah al-Jumuah verse 10, ash-Shaf verses 10-11 and al-Qashash verse 77. (2) The view of the hadith about entrepreneurial motivation can be found in the hadith text narrated by Imam al-Bukhari sourced from Miqdam Ibn Ma'dikarib ra. and narrated by Ibn Asakir who sourced from ra. (3) The view of the motivation of an entrepreneur is the command to scatter on earth rather than stay in place, then the command to seek the gift of God and remember God a lot. In addition, an entrepreneur is required to help each other or help in goodness and not enrich themselves so as to balance the needs of the world and the hereafter.Abstracts and keywords written in two languages (Indonesian and English). The length of each abstract is 200-250 words, instead of keywords 3-5 words count. Abstracts contain minimal problems, objectives, methods, concepts, and results of research and discussion